(untitled) (Iranian Journal of Kidney Diseases, 2014)
The present survey aims at studying the opinions of three famous medical scholars in history (Rhazes, Avicinna, and Jorjani) on the diagnosis of diseases via urine examination and their compatiblity with modern science. Refering to original authentic sources in traditional medicine, including Al-Hawi (The Virtuous Life), Zakhireh-i Kharazmshahi (Thesaurus of the Shah of Khwarazm), and Al-Canon fi al Tibb (The Canon on Medicine), we compared the ideas of the authors with modern medicine. In traditional medicine, physicians would pay attention to the methods of urine collection and urinary features such as color, consistency, volume, frequency, odor, and foam as the means of diagnosis, all of which still serve as the bases for today’s diagnostic approach. Moreover, symptoms of the diagnosis of the disease through urine are consistent in tradition and modern medicine; some examples are blood in the urine (hematuria), decreased urine output (oliguria), change in urine color together with headache (Alport syndrome), diluted urine (tubular dysfunction in reabsorption of water or initial polydipsy), and urinary floor with tiny bubbles (one of the main symptoms of proteinuria).